Characteristics Weak Galerkin Finite Element Methods for Convection-Dominated Diffusion Problems. (27th May 2014) - Zhu, Ailing; Xu, Qiang; Jiang, Ziwen
Abstract : The weak Galerkin finite element method is combined with the method of characteristics to treat the convection-diffusion problems on the triangular mesh. The optimal order error estimates in H 1 and L 2 norms are derived for the corresponding characteristics weak Galerkin finite element procedure. Numerical tests are performed and reported.